Lymphocyte-to-monocyte ratio after primary surgery is an independent prognostic factor for patients with epithelial ovarian cancer: A propensity score matching analysis - Hu, Qian; Shen, Guihua; Li, Ye; Xie, Ya; Ma, Xiao; Jiang, Lijuan; Lv, Qiubo (Frontiers in Oncology, 2023)
Background: The aim of this study was to elucidate the prognostic value of the preoperative lymphocyte-to-monocyte ratio (LMR) in epithelial ovarian cancer (EOC) patients after primary surgery using propensity score matching (PSM) analysis. Methods: We retrospectively reviewed consecutive EOC patients who underwent primary surgery between January 2008 and December 2019. Patients were divided into two groups according to the optimal cutoff value of the preoperative LMR. PSM (1:1) was conducted to eliminate the confounding factors. The Cox proportional hazards model and Kaplan–Meier estimator were employed to investigate the potential prognostic factors. Results: A total of 368 EOC patients were included in this study. The optimal cutoff value of LMR was identified as 4.65. A low preoperative LMR was significantly correlated with low albumin, high CA125 level, more blood loss, a high proportion of ascites, advanced FIGO stage, and poor differentiation (all p < 0.05). After matching, the Kaplan Meier curves showed that the LMR < 4.65 group experienced significantly shorter OS (p = 0.015). Multivariate Cox analysis revealed that low LMR (HR = 1.49, p = 0.041), advanced FIGO stage (HR = 5.25, p < 0.001) and undefined residual disease (HR = 3.77, p = 0.002) were independent factors for predicting poor OS. A forest plot revealed that LMR had better prognostic value in younger EOC patients with BMI ≥ 25 kg/m2, albumin ≥ 35 g/L, CA125 ≥ 35 U/L, optimal surgery and reception of completed chemotherapy. Additionally, low LMR patients with incomplete chemotherapy had a shorter median OS compared with those who completed (48.5 vs. 105.9 months, p = 0.026). Conclusion: LMR could be used as an independent prognostic factor for EOC patients after primary surgery, and the noticeable negative effect of LMR was observed among EOC patients with age < 65, good preoperative nutritional status, more aggressive tumor biology and who underwent optimal surgery. Completing adjuvant chemotherapy is essential to improve the survival outcome of EOC patients with LMR < 4.65 after surgery.